On the coupled dynamics of vertical cladding panels and industrial frame structures subject to out-of-plane seismic loading - Foti, Francesco; Dal Lago, Bruno; Martinelli, Luca (Engineering structures, 2023)
Industrial facilities typically consist in large-span single-storey prefabricated buildings having a rectangular floor space. Frame structures made with either steel, timber or precast concrete members are mostly employed to support the roof, while cladding panels create the building enclosure. Their interaction with the frame typically plays a relevant role in the overall building dynamics, potentially leading under seismic excitation to both local and global collapses. Experience shows that a critical component failure is that of the panel-frame connection. Current design approaches classify the panels as “non-structural members” and the forces at the connections induced by the out-of-plane seismic loading are evaluated with approximate expressions. Neglecting the dynamic interaction between the panel and the frame, however, may lead to an oversimplified description of the mechanical problem and inaccurate estimates of the forces at the connections. To overcome these drawbacks, in this work a different approach is pursued in which the interaction between the fundamental sway mode of the frame and the out-of-plane motion of the cladding panel is studied within a rigorous mechanical setting. The focus is on the very frequent case of vertical cladding panels, supported at the ground and retained out-of-plane by the frame. Starting from the development of the equations of motion for the coupled frame-panel structure, a minimal set of parameters controlling the dynamics of the system is identified. The spectral properties of the structure are analytically investigated to gain a clear insight on the coupled frame-panel structure. This is characterized by frequency veering and hybridization between the mode deforming the frame and the local modes of the panel. The system response for seismic excitation, then, is studied with a stochastic approach. Parametric analyses focusing on the values of the forces at the top and bottom connections of the panel and on the lateral displacement of the frame show that while the frame drift is controlled mainly by the first mode of the coupled frame-panel system, the top and bottom connection forces of the panel require at least consideration of the first two modes of the coupled system. This information is of great importance in deriving a reduced model of the coupled system. The proposed procedure allows for a thorough understanding of the coupled system dynamic response, and represents a viable alternative to derive the design response quantities of interest. •Dynamic interaction between frames and vertical cladding panels is investigated.•A minimal set of parameters controlling the dynamics of the system is identified.•Seismic response of coupled frame-panel systems is studied in a stochastic framework.